IMPLEMENTASI SAKIP DALAM PERENCANAAN STRATEGIS DI DPMPTSP NAKER KOTA MOJOKERTO - Putri, Rachmawati Herdianti; Rahaju, Tjitjik (Publika, 2023)
Systematic performance reporting in the form of the Government Agency Performance Accountability System (SAKIP) is a form of responsibility carried out by government agencies to the central government for their performance achievements during 1 period. In accordance with the Presidential Regulation of the Republic of Indonesia Number 29 of 2014, government agencies which are also regional apparatuses have an obligation to participate in the implementation of SAKIP. Strategic planning is the basis for implementing SAKIP as well as stated in the regulation. Then it was lowered into PAN-RB Ministry Regulation Number 88 of 2021, the AKIP evaluation was carried out to obtain information regarding the implementation of SAKIP. The standards for implementing SAKIP are clearly stated in these regulations. The purpose of this study was to obtain a description of the implementation of SAKIP at theDPMPTSP NAKER in Mojokerto City in determining strategic planning. The research will be studied using the top-down policy implementation model theory according to Van Meter and Van Horn. The research method used is descriptive with a qualitative approach. Data collected using observation techniques, interviews, and documentation. Determination of the informant sample using purposive sampling and snowball sampling techniques. The results of the study show that in the implementation of SAKIP DPMPTSP NAKER has implementation standards which have been clearly stated on the applicable legal basis. Communication and the existence of competent and quality resources are very important so that they can control the implementation of SAKIP properly and on target. The leadership's role in supporting the implementation of SAKIP DPMPTSP NAKER can affect agency performance. As well as support from experts for the implementation of SAKIP is also needed for the stability of the value of SAKIP at DPMPTSP NAKER Mojokerto City.